Transaction costs and tradable permits: Empirical evidence from the EU emissions trading scheme - Peter Heindl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
In this paper, transaction costs in the EU emissions trading scheme (EU ETS) are examined empirically based on survey data from German companies. Transaction costs from measurement, reporting and verification (MRV) of emissions, permit trading and general informational costs are considered. Transaction costs from MRV and permit trading are of non-linear form and dependent on annual emission and trading volumes based on OLS and nonparametric estimation. As a consequence of non-linear transaction costs, welfare losses occur compared to a first-best setup under zero transaction costs. In practice, smaller emitters will emit less (abate more) compared to larger emitters and vice versa due to economies of scale in the management of emissions trading. The results further imply that optimal firm size might be influenced by transaction costs in the EU ETS because of relatively high average transaction costs amongst smaller emitters. Overall annual transaction costs in the EU ETS in Germany are estimated to be EUR 8.7 million.
urn:nbn:de:bsz:180-madoc-322019
Keywords: Q52; H23; D23; 330; Emissions Trading; Transaction Costs; EU ETS